Animation Techniques and Image Aesthetics in the Rewriting for the Big Screen of Fantastic Children and Youth Literature Broadcast in Spain (1996-2019) - García-Pedreira, Rocío; Reis da Silva, Sara (Íkala, Revista de Lenguaje y Cultura, 2022)
Currently, there is a lack of research and theoretical studies on children and family movies, which makes it difficult to point out curricular developments on the subject which allow the updating of teacher training programs and the use of those productions in the classroom. Given this gap, this work aims to inquire about the incidence of animation techniques on the development of children and family movies which rewrote children's and youth literature for the big screen since the end of the last century, in Spain. In this regard, a mixed methodological design is proposed, based on ex post facto research with a descriptive orientation and content analysis of verbo-iconic (films) and printed (literary works) products. The results indicate that there is a growing trend for rewriting in real image, and for the use of animation techniques that introduce visual effects with the purpose of overcoming the difficulties inherent in the process of recreating, on the big screen, events, characters or impossible scenarios and making them pass for real. In any case, the adaptation phenomenon is a constant and assiduous reality that conditions and determines the process of socialization of the individual. Therefore, it is fundamental to study this phenomenon to overcome educational deficiencies in this sense and to develop effective didactic programming.